A mouse model of acute biliary pancreatitis induced by retrograde pancreatic duct infusion of Na-taurocholate. Issue 11 (25th June 2007) - Laukkarinen, Johanna M; Van Acker, Gijs J D; Weiss, Eric R; Steer, Michael L; Perides, George
Abstract : Objective: Most mechanistic studies of pancreatitis in mice employ the secretagogue-induced model. The currently reported studies were designed to develop an alternative, and possibly more clinically relevant, mouse model of pancreatitis. Design: Na-taurocholate (10–50 μl, 1–5%) in saline, or saline alone, was retrogradely infused into the mouse pancreatic duct. The animals were killed 6–24 hours later and the severity of pancreatitis in the pancreatic head and tail was examined by quantitating hyperamylasemia, pancreatic edema, acinar cell necrosis, and pancreatic inflammation. In addition, intrapancreatic activation of trypsinogen, generation of IL-6, intrapulmonary sequestration of neutrophils, and alterations in lung compliance were evaluated. The effects of Na-taurocholate on in-vitro acinar cell calcium transients, viability, and trypsinogen activation were examined. Results: Little or no evidence of pancreatitis was observed in mice infused with saline alone or in the tail of pancreata removed from animals infused with Na-taurocholate. In the head of the pancreas, evidence of pancreatitis was observed 12–24 hours after infusion of 20–50 μl 2–5% Na-taurocholate and the earliest morphological changes involved terminal duct and acinar cells. Intrapancreatic trypsin activity was transiently elevated within 5 minutes of Na-taurocholate infusion and pancreatic IL-6 levels were elevated 24 hours later. Under in-vitro conditions, Na-taurocholate triggered pathological acinar cell calcium transients, cell death, and calcium-dependent trypsinogen activation. Conclusion: This clinically relevant model of acute biliary pancreatitis yields reproducible results and its severity can be easily manipulated. It is ideally suited for use in mechanistic studies employing genetically modified mouse strains.